2021
DOI: 10.1016/j.stemcr.2021.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Germ Cell Development: From Mechanism to In Vitro Reconstitution

Abstract: The germ cell lineage gives rise to totipotency and perpetuates and diversifies genetic as well as epigenetic information. Specifically, germ cells undergo epigenetic reprogramming/programming, replicate genetic information with high fidelity, and create genetic diversity through meiotic recombination. Driven by advances in our understanding of the mechanisms underlying germ cell development and stem cell/reproductive technologies, research over the past 2 decades has culminated in the in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 136 publications
(158 reference statements)
0
30
0
Order By: Relevance
“…Curiously however, we found that these cells do not express the definitive endoderm marker FOXA2 (Fig 1A). In primates, SOX17 does not only mark definitive endoderm but also primordial germ cells (PGCs), which moreover form close to the interface of the posterior epiblast and amnion, with their precise origin in human still a point of debate(Saitou 2021; Hancock et al 2021). This suggests these cells could be PGC-like cells (PGCLCs) instead.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curiously however, we found that these cells do not express the definitive endoderm marker FOXA2 (Fig 1A). In primates, SOX17 does not only mark definitive endoderm but also primordial germ cells (PGCs), which moreover form close to the interface of the posterior epiblast and amnion, with their precise origin in human still a point of debate(Saitou 2021; Hancock et al 2021). This suggests these cells could be PGC-like cells (PGCLCs) instead.…”
Section: Resultsmentioning
confidence: 99%
“…The identity of the outer ring of cells has been a source of debate and is important in the context of PGCLC induction because PGCs have been found to derive from the amnion in cynomolgous monkeys, while their origin in human remains unclear(Saitou 2021; Hancock et al 2021). We argue that these cells are amnion-like and named them AmLC.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies in humans also suggest that BMP as well as Wnt signals induce mesodermal precursor cells to become PGCs around the third week of gestation (82,118). By E7.2, a population of approximately 40 PGCs is apparent in mice (82,118). Between E7.5 and 10.5 these PGCs migrate Mechanisms of organelle selection.…”
Section: Mitochondrial Dna In Mammalian Germline Developmentmentioning
confidence: 99%
“…In mice, germ cells are first formed in the proximal posterior epiblast at the onset of gastrulation around embryonic day 6 (E6.0) (reviewed in 82,118). The secretion of BMP (bone morphogenetic protein) signals from the extraembryonic ectoderm and the visceral endoderm induces a group of posterior epiblast cells to become primordial germ cells (PGCs) (82,118). In vitro studies in humans also suggest that BMP as well as Wnt signals induce mesodermal precursor cells to become PGCs around the third week of gestation (82,118).…”
Section: Mitochondrial Dna In Mammalian Germline Developmentmentioning
confidence: 99%
See 1 more Smart Citation